A Preliminary Study: Human Fibroid Stro-1+/CD44+ Stem Cells Isolated From Uterine Fibroids Demonstrate Decreased DNA Repair and Genomic Integrity Compared to Adjacent Myometrial Stro-1+/CD44+ Cells. (May 2019) - Prusinski Fernung, Lauren E.; Al-Hendy, Ayman; Yang, Qiwei
Context: Although uterine fibroids (UFs) continue to place a major burden on female reproductive health, the mechanisms behind their origin remain undetermined. Normal myometrial stem cells may be transformed into tumor-initiating stem cells, causing UFs, due to unknown causes of somatic mutations in MED12, found in up to 85% of sporadically formed UFs. It is well established in other tumor types that defective DNA repair increases the risk of such tumorigenic somatic mutations, mechanisms not yet studied in UFs. Objective: To examine the putative cause(s) of this stem cell transformation, we analyzed DNA repair within stem cells from human UFs compared to those from adjacent myometrium to determine whether DNA repair in fibroid stem cells is compromised. Design: Human fibroid (F) and adjacent myometrial (Myo) stem cells were isolated from fresh tissues, and gene expression relating to DNA repair was analyzed. Fibroid stem cells differentially expressed DNA repair genes related to DNA double- (DSBs) and single-strand breaks. DNA damage was measured using alkaline comet assay. Additionally, DNA DSBs were induced in these stem cells and DNA DSB repair evaluated (1) by determining changes in phosphorylation of DNA DSB-related proteins and (2) by determining differences in γ-H2AX foci formation and relative DNA repair protein RAD50 expression. Results: Overall, F stem cells demonstrated increased DNA damage and altered DNA repair gene expression and signaling, suggesting that human F stem cells demonstrate impaired DNA repair. Conclusions: Compromised F stem cell DNA repair may contribute to further mutagenesis and, consequently, further growth and propagation of UF tumors.